Neuroprotective Effects of Phenolic Constituents from Drynariae Rhizoma - Jin Sung Ahn; Chung Hyeon Lee; Xiang-Qian Liu; Kwang Woo Hwang; Mi Hyune Oh; So-Young Park; Wan Kyunn Whang (MDPI AG, 2024)
This study aimed to provide scientific data on the anti-Alzheimer's disease (AD) effects of phenolic compounds from Drynariae Rhizoma (DR) extract using a multi-component approach. Screening of DR extracts, fractions, and the ten phenolic compounds isolated from DR against the key AD-related enzymes acetylcholinesterase (AChE), butyrylcholinesterase (BChE), β-site amyloid precursor protein cleaving enzyme 1 (BACE1), and monoamine oxidase-B (MAO-B) confirmed their significant inhibitory activities. The DR extract was confirmed to have BACE1-inhibitory activity, and the ethyl acetate and butanol fractions were found to inhibit all AD-related enzymes, including BACE1, AChE, BChE, and MAO-B. Among the isolated phenolic compounds, compounds (2) caffeic acid 4-O-β-D-glucopyranoside, (6) kaempferol 3-O-rhamnoside 7-O-glucoside, (7) kaempferol 3-o-b-d-glucopyranoside-7-o-a-L-arabinofuranoside, (8) neoeriocitrin, (9) naringin, and (10) hesperidin significantly suppressed AD-related enzymes. Notably, compounds 2 and 8 reduced soluble Amyloid Precursor Protein β (sAPPβ) and β-secretase expression by over 45% at a concentration of 1.0 μM. In the thioflavin T assay, compounds 6 and 7 decreased Aβ aggregation by approximately 40% and 80%, respectively, and degraded preformed Aβ aggregates. This study provides robust evidence regarding the potential of DR as a natural therapeutic agent for AD, highlighting specific compounds that may contribute to its efficacy.